NAT10 Knockdown Improves Cisplatin Sensitivity in Non‐Small Cell Lung Cancer by Inhibiting the TRIM44/PI3K/AKT Pathway - Sun, Qi; Yang, Xiansong; Wang, Ye; Yang, Kejia; Weng, Yuan (Thoracic cancer, 2025)
ABSTRACT Background Non‐small cell lung cancer (NSCLC) is a leading cause of cancer‐related deaths worldwide, and cisplatin (DDP) resistance remains a significant challenge in NSCLC treatment. Methods Quantitative reverse transcription polymerase chain reaction (qRT‐PCR) was used to analyze NAT10 and tripartite motif containing 44 (TRIM44) mRNA levels. Western blotting assay was used to detect protein expression. Cell viability was analyzed by a cell counting kit‐8 assay. Cell proliferation, apoptosis, invasion, and stem‐like traits were assessed using a 5‐Ethynyl‐2′‐deoxyuridineassay, flow cytometry, Transwell invasion assay, and sphere formation assay, respectively. The association between NAT10 and TRIM44 was identified by an RNA immunoprecipitation assay. A xenograft mouse model was established to evaluate the effect of NAT10 silencing on DDP sensitivity in vivo. Results NAT10 expression was upregulated in DDP‐resistant NSCLC tissues and cells. NAT10 knockdown enhanced DDP sensitivity in DDP‐resistant NSCLC cells, accompanied by decreased protein expression of multidrug resistance 1 (MDR1). The silencing of NAT10 also inhibited the proliferation, invasion, and stem‐like traits of DDP‐resistant NSCLC cells, while inducing cell apoptosis. However, NAT10 overexpression displayed the opposite effects. Moreover, NAT10 maintained TRIM44 mRNA stability in an ac4C‐dependent manner. TRIM44 overexpression reversed the NAT10 knockdown‐induced effects on DDP sensitivity and the malignant progression of NSCLC cells. In addition, NAT10 silencing inactivated the PI3K/AKT pathway by regulating TRIM44 in DDP‐resistant NSCLC cells. The treatment of the PI3K/AKT pathway inhibitor, LY294002, mitigated the effects of TRIM44 overexpression on DDP sensitivity and NSCLC cell progression. Further, NAT10 knockdown improved the sensitivity of tumors to DDP in vivo. Conclusion NAT10 knockdown improved DDP sensitivity in NSCLC by inhibiting the TRIM44/PI3K/AKT pathway, which may have significant clinical implications for overcoming DDP resistance in NSCLC treatment. NAT10 expression is elevated in DDP‐resistant NSCLC cells. The enhanced expression of NAT10 leads to an increase in TRIM44 expression through an ac4C‐dependent mechanism, which subsequently activates the PI3K/AKT pathway. This activation, in turn, reduces the sensitivity of NSCLC cells to DDP, inhibits apoptosis, and fosters cell proliferation, invasion, and sphere formation.